2009
DOI: 10.1371/journal.pcbi.1000542
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Selection in Models of Prebiotic Evolution II: A Direct Comparison of Compartmentalization and Spatial Self-Organization

Abstract: Multilevel selection has been indicated as an essential factor for the evolution of complexity in interacting RNA-like replicator systems. There are two types of multilevel selection mechanisms: implicit and explicit. For implicit multilevel selection, spatial self-organization of replicator populations has been suggested, which leads to higher level selection among emergent mesoscopic spatial patterns (traveling waves). For explicit multilevel selection, compartmentalization of replicators by vesicles has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
123
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(142 citation statements)
references
References 57 publications
(73 reference statements)
13
123
1
Order By: Relevance
“…In all experiments, the affinity of replicases towards replicases was equal to a R = 0.7 and the replicases were catalytically active regardless of their folded state. The value of a R differs from the value that was used in the experiments by Takeuchi and Hogeweg [33], where it was set to 0.6. We also examined the value a R = 0.6; however, closer investigation showed that while a slightly higher value of this parameter equal to 0.7 does not change the characteristics of the system, it does give better results in terms of a more stable coexistence between parasites and replicases, meaning that we could more easily observe the emerging behaviors in the system.…”
Section: Resultsmentioning
confidence: 99%
“…In all experiments, the affinity of replicases towards replicases was equal to a R = 0.7 and the replicases were catalytically active regardless of their folded state. The value of a R differs from the value that was used in the experiments by Takeuchi and Hogeweg [33], where it was set to 0.6. We also examined the value a R = 0.6; however, closer investigation showed that while a slightly higher value of this parameter equal to 0.7 does not change the characteristics of the system, it does give better results in terms of a more stable coexistence between parasites and replicases, meaning that we could more easily observe the emerging behaviors in the system.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of cells is a key early step in the evolution of life, but it is not yet clear just how early this step is. It is quite difficult to compare models of spatial clustering and protocells because they tend to be formulated in different ways, although see [43] for a good attempt at doing this.…”
Section: Discussionmentioning
confidence: 99%
“…This process protects the population from extinction and results in evolutionary dynamics yielding a stable quasispecies at the level of compartments 162 . The SCM is inherently stable against parasites: it has the ability to select against inferior and select for superior mutants [163][164][165][166] . The cells of the SCM are individuals subject to selection and are thus evolutionary units.…”
Section: Ii/3 Active Compartmentalizationmentioning
confidence: 99%